2020
DOI: 10.3390/ijerph17186835
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Employment, Mental Health, and Suicidal Behavior: A Propensity Score Matching Approach

Abstract: This study aimed to confirm the relationships between part-time work experience, mental health, and suicidal behavior in adolescents. The impact of part-time work in this population is a controversial topic, perhaps because of the sociocultural background-related inconsistencies in previous results. In this cross-sectional study, which involved a secondary analysis of data from the 11th–13th Korea Youth Risk Behavior Web-Based Surveys, conducted among 800 middle and high schools by the Korean government, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…The correlation between precarious employment and the symptoms of depression and dysthymia was confirmed by studies conducted in Italy [ 30 ]. Another study showed that part-time work experience had a direct correlation with poor mental health and suicidal behavior [ 31 ]. In turn, Vives et al [ 32 ], who analyzed Spanish workers employed on temporary contracts, confirmed that people with short-term employment contracts were more likely to suffer from depression than those in permanent employment.…”
Section: Literature Background and Hypothesesmentioning
confidence: 99%
“…The correlation between precarious employment and the symptoms of depression and dysthymia was confirmed by studies conducted in Italy [ 30 ]. Another study showed that part-time work experience had a direct correlation with poor mental health and suicidal behavior [ 31 ]. In turn, Vives et al [ 32 ], who analyzed Spanish workers employed on temporary contracts, confirmed that people with short-term employment contracts were more likely to suffer from depression than those in permanent employment.…”
Section: Literature Background and Hypothesesmentioning
confidence: 99%
“…Теоретической и методологической базой исследования послужили работы зарубежных [4][5][6] и отечественных ученых [1,[7][8][9][10][11], а также комплекс статистических данных [3]. Достижение поставленной цели осуществлялось с применением метода рядов динамики основных индек-сов, подлежащих расчету в контексте переменного аспекта, позволяющего не только отразить в динамике формирование коэффициента нагрузки занятой молодежи 15-19 лет, но и выявить допустимые потенциальные возможности его активного роста.…”
Section: материал и методы исследованияunclassified
“…These changes make adolescents vulnerable to mental health issues, high-risk behaviors, suicidal ideation, and suicidal behavior. 6 Several factors have been identified as potential influences on suicidal attempts during adolescence, including previous suicide history, 1 , 7 , 8 psychiatric disorders, 1 , 2 , 9 , 10 and substance abuse disorders. 2 …”
Section: Introductionmentioning
confidence: 99%